Chemerin Added to Endothelin-1 Promotes Rat Pulmonary Artery Smooth Muscle Cell Proliferation and Migration - Hanthazi, Aliénor; Jespers, Pascale; Vegh, Grégory; Dubois, Christine; Hubesch, Géraldine; Springael, Jean-Yves; Dewachter, Laurence; Mc Entee, Kathleen (Frontiers in Physiology, 2020)
Background: While chemerin has been shown to increase proliferation and migration of systemic vascular smooth muscle cells (SMCs) contributing therefore to the development of hypertension, this remains to be clarified for the pulmonary circulation. Methods: Expression of chemerin and its three receptors (CMKRL1, CCRL2, GPR1) was examined by immunohistochemistry and RTq-PCR in lungs, pulmonary artery and thoracic aorta from Wistar rats. Primary cultured rat pulmonary artery and thoracic aorta SMCs treated with recombinant chemerin (tested from 5.10-9 to 10-7 mol/L) were assessed for proliferation and migration (both with 10-7 mol/L endothelin-1), as well as for staurosporine-induced apoptosis. Results: In pulmonary artery and thoracic aorta, CMKLR1 expression was detected in both endothelial cells and SMCs. In primary cultured pulmonary artery SMCs, chemerin and its three receptors were expressed and CMKLR1 expression was higher than those of CCRL2 and GPR1. Chemerin added to endothelin-1 increased pulmonary artery SMC proliferation, while chemerin or endothelin-1 alone did not. This effect was less pronounced in thoracic aorta SMCs. Chemerin induced pulmonary artery and thoracic aorta SMC migration, which was exacerbated by endothelin-1 and more pronounced in thoracic aorta SMCs. Chemerin concentration-dependently reduced staurosporine-induced apoptosis in both pulmonary artery and thoracic aorta SMCs. In pulmonary artery SMCs, endothelin-1 treatment increased expression of CMKLR1, CCRL2 and GPR1, while these expressions were not altered in thoracic aorta SMCs. Conclusion: Chemerin/CMKRL1 signaling, in conjunction with a key mediator in the pathogenesis of pulmonary hypertensive diseases, endothelin-1, stimulated proliferation and migration, and increased resistance to apoptosis in rat primary cultured pulmonary artery SMCs. Our results suggest that this signaling could play a role in pulmonary artery remodeling observed in pulmonary hypertension.